HUBUNGAN ANTARA PRODUK KALSIUM X FOSFAT SERUM DENGAN PENYAKIT ARTERI PERIFER PADA PASIEN HEMODIALISIS REGULER DI RSUP SANGLAH DENPASAR - Wulandari, Dewi Catur; Raka Widiana, I G; SL, Jodi; Sudhana, I W; Suwitra, Ketut (journal of internal medicine, 2007)
Peripheral Arterial Occlusive Disease (PAOD) is common among patients undergoing hemodialysis (HD). In the generalpopulation, DM, male, cigarette smoking, advanced age, hypertension and dyslipidemia are the most important risk factorsfor PAOD. Recently, some studies in patients with regular HD found evidences that PAOD associated with increase of calciumand phosphate serum level and increase of Ca.P product due to secondary hyperparatiroidism. A cross-sectional study was doneon 46 regular HD patients to evaluate prevalence of PAOD among patients who are undergoing regular HD and their associationbetween Ca.P product. Morning fasting plasma were taken for lipid profile, blood sugar, blood urea nitrogen, serum creatinin,albumin level, Ca, inorganic P. Ankle-brachial index (ABI) of blood pressure as measured after dialysis session using Va-SeraVS-100. Fourty six (26 males, 20 females) regular HD patients, age 50.95 ± 9.90 years, duration of HD 27.7 ± 22 months wereincluded in this study. Using ABI < 0.9 as cut off value for the presence of PAOD, 15.2% had PAOD. Means of Ca serum levelwas 9.04 ± 0.76 mg/dl, phosphate serum level was 56.48 ± 23.90 mg/dl. Using 55 or more as cut off value for abnormal concentrationof Ca.P product, 47.7% patients had abnormal Ca.P product. Three of 21 patients with Ca.P 55 had PAOD and 4 of 23patients with Ca.P < 55 had PAOD ( OR 0.79 with 95% CI : 0.15 ? 4.04 for patients with Ca.P < 55 ). Using logistic regression tocontrol Ca and P levels, Ca.P 55 tend to associate with increased risk of PAOD (OR 6.22 ; 95% CI : 0.23 ? 167.71)More than fifteen percent of patients with regular HD had PAOD. More than fourty seven percent of patients had abnormal Ca.P.Patients with Ca.P 55 tend to associated with increased risk of PAOD (OR 6.22 ; 95% CI : 0.23 ? 167.71)